LncRNA HIF2PUT inhibited osteosarcoma stem cells proliferation, migration and invasion by regulating HIF2 expression - Ding Zhao; Sisi Wang; Xu Chu; Dongfeng Han (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Purpose The function of lncRNAs in cancer stem cells (CSCs) remains to be elucidated. The present study aimed to investigate the regulating role of a novel lncRNA, hypoxia-inducible factor-2α (HIF-2α) promoter upstream transcript (HIF2PUT), in osteosarcoma stem cells.Methods The expression of lncRNA HIF2PUT and HIF-2α in osteosarcoma stem cell lines and tissues was monitored by real-time PCR and western blot. The proliferation ability was examined by MTT assay when HIF2PUT overexpression or knockdown. The self-renewing capabilities of the cells were assessed by spheroid formation assay. The migration and invasion of cells were monitored by wound-healing assay and transwell cell assay, respectively. The correlation of HIF2PUT and HIF-2α expression was determined in osteosarcoma cancer tissues.Results LncRNA HIF2PUT and HIF-2α were downregulated in osteosarcoma cell lines. HIF2PUT exhibited a significant decline in proliferation capacity. Wound healing and transwell assays showed that lncRNA overexpression inhibited osteosarcoma stem cell migration and invasion. HIF2PUT inhibited sphere formation in osteosarcoma stem cells. Increased HIF2PUT expression inhibited the enrichment of CD133 in osteosarcoma stem cells. There was a strong positive correlation between relative HIF2PUT level and relative HIF-2α level in the 30 paired osteosarcoma cancer tissues.Conclusions Overexpression of lncRNA HIF2PUT significantly attenuated the proliferation, migration and invasion of osteosarcoma stem cells. Furthermore, we demonstrated that lncRNA overexpression inhibited the sphere-formation of osteosarcoma stem cells by downregulating HIF-2α. These findings suggest that lncRNA HIF2PUT may act as a tumour suppressor in osteosarcoma. LncRNA HIF2PUT/HIF-2α may be a novel therapeutic target in the treatment of osteosarcoma.